Research on visual search strategies during apparatus throw-and-catch in group rhythmic gymnastics - Zhou, Chuncen; Cai, Yujun; Li, Kai; Zhang, Xinmiao; Tang, Changhao (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the visual search characteristics and strategies of expert rhythmic gymnasts during apparatus throw-and-catch tasks under different apparatus types and difficulty levels, in order to provide theoretical support for optimizing routine choreography and designing effective visual training programs.MethodsFifteen rhythmic gymnasts at or above the national first-class level were recruited. Tobii Pro Glasses 3 wearable eye tracker was used to collect eye movement data during four throw-and-catch tasks of varying difficulty levels (Hoop 1–3, Ball 4). Global eye movement metrics (total duration of whole fixations, number of whole fixations, number of saccades) and area of interest (AOI) indicators (total duration of fixation, total duration of visit, total duration of glances, etc.) were analyzed using Kruskal–Wallis tests and Bonferroni-corrected post-hoc comparisons.ResultsAs task difficulty increased, athletes showed significantly longer total fixation duration, more fixation points, and more saccades (p < 0.001, η2 = 0.105); Under the same difficulty level, hoop-related tasks imposed a higher visual search load compared to ball tasks (p < 0.05); AOI analysis indicated significantly greater visual attention during the catching phase than the throwing phase. In high-difficulty conditions, athletes demonstrated more efficient visual strategies, such as shorter fixation times and reduced saccade paths.ConclusionExpert rhythmic gymnasts actively adjust their visual strategies based on task complexity and apparatus characteristics, showing goal-oriented behaviors and evidence of experience transfer. Visual search efficiency is jointly influenced by movement difficulty and apparatus type. It is recommended that future training incorporates task-specific visual training programs to enhance throw-and-catch success rates and overall performance.